(untitled) (Ustozlar uchun, 2024)
Introduction: In an era of increasing economic uncertainty and regional disparities, the role of local governments in promoting socio-economic stability has never been more critical. One of the key tools at their disposal is the local budget, which can be strategically managed to foster sustainable development and stability. This article explores the topic of local budget revenue augmentation and its potential to strengthen socio-economic stability in regions.